FOLKLORE’S IMPACT ON CONTEMPORARY POETRY (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
ANNOTATION: For many years, poets have drawn inspiration from folklore, which offers a wealth of material to explore issues of custom, identity, and cultural history. Poetry from the past and present is greatly influenced by folklore, as poets utilize myths, stories, and folk customs to create works that have a lasting impact. Poets interact with ageless stories and symbols that relate to common human experiences and emotions by incorporating folklore into their poems. To explore themes of power, fate, and metamorphosis, poets frequently use folkloric characters—such as gods, heroes, and monsters—in their poetry. Poets may access a rich reservoir of symbolic meaning that transcends personal experiences and speaks to the common challenges and victories of humanity by drawing from these archetypal personalities.